2022
DOI: 10.1186/s40168-022-01306-y
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered Odoribacter laneus improves glucose control and inflammatory profile in obese mice by depleting circulating succinate

Abstract: Background Succinate is produced by both human cells and by gut bacteria and couples metabolism to inflammation as an extracellular signaling transducer. Circulating succinate is elevated in patients with obesity and type 2 diabetes and is linked to numerous complications, yet no studies have specifically addressed the contribution of gut microbiota to systemic succinate or explored the consequences of reducing intestinal succinate levels in this setting. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 80 publications
1
47
0
Order By: Relevance
“…Odoribacter has been found to be negatively associated with the expression of intestinal epithelial tight junction proteins, suggesting a link with impairing mucosal barrier function in rats [ 39 ]. However, Huber-Ruano et al (2022) showed that one strain of O. laneus , DSM 22474 A, has beneficial anti-inflammatory and metabolic properties in obese mice [ 40 ]. Collectively, our results strongly suggest that the effects of this species may be strain-specific and indicate the need of comprehensive evaluation before pursuing Odoribacter strains for treating type 2 diabetes in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Odoribacter has been found to be negatively associated with the expression of intestinal epithelial tight junction proteins, suggesting a link with impairing mucosal barrier function in rats [ 39 ]. However, Huber-Ruano et al (2022) showed that one strain of O. laneus , DSM 22474 A, has beneficial anti-inflammatory and metabolic properties in obese mice [ 40 ]. Collectively, our results strongly suggest that the effects of this species may be strain-specific and indicate the need of comprehensive evaluation before pursuing Odoribacter strains for treating type 2 diabetes in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Succinate is a cometabolite produced by both hosts and microbes, and it is typically identified at low levels in the intestinal lumen, likely due to its cross-feeding relationships ( Connors et al., 2018 ). Substantial evidence has indicated that succinate concentrations increase under conditions of hypoxia, stress, inflammation, and changes in intestinal microorganisms ( Nagao-Kitamoto et al., 2016 ; Macias-Ceja et al., 2019 ; Banerjee et al., 2020 ; Huber-Ruano et al., 2022 ). It has been widely reported in previous studies that changes in the intestinal flora are closely related to the development of NEC ( He et al., 2021 ; Liu et al., 2022a ; Samara et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Odoribacter laneus (O. laneus) is a Gram-negative anaerobe rod that was isolated from the human feces of a healthy Japanese adult donor in 2010 [ 125 ]. Very recently, in 2022, Hueber-Ruano et al characterized O. laneus as an NGP due to its ability to ameliorate insulin sensitivity and decrease inflammatory markers in a mouse model [ 126 ]. By administering O. laneus through oral gavage in obese mice, they documented a significant reduction in serum succinate levels.…”
Section: Preventive and Therapeutic Potential Of Ngps In Obesity And ...mentioning
confidence: 99%